Velocity specificity of resistance training: Actual movement velocity versus intention to move explosively - Kawamori, N.; Newton, R. U. (Strength and Conditioning Journal, 2006)
In summary, we conclude that (a) classic theory of velocity specificity may not necessarily apply to isoinertial training; (b) both the intention to move explosively and the actual movement velocity are important and crucial stimuli that elicit high-velocityspecific neuromuscular adaptations to resistance training; and (c) athletes are recommended to use a range of training loads and attempt to lift a given load as quickly as possible, which should be coupled with the practice of actual sport movements to maximize the transfer of training effect. We also recommend the use of resistance-training movement profiles that maximize the acceleration phase throughout the range of movement and minimize the deceleration phase. Examples of such exercises include weightlifting movements (e.g., clean, power snatch) and ballistic training exercises (e.g., jump squat, bench press throw).